Evaluación de una mezcla forrajera (ray-grass, pasto azul, trébol blanco y llantén), a los 30 y 45 días de rebrote, más suplemento concentrado en vacas lactantes en la hcda. San Jorge, parroquia Machachi – sector Aloag - Rocha Toctaguano, Silvia Graciela (2011)
In this thesis we evaluated the use of a particular mixture of grass feed (Lolium Perenne, Setaria anceps, Trifolium Repens, Plantago Lanceolata, ,), regrown 30- days and 45-days after the initial cut, supplemented with concentrated feed, for milk cattle from San Jorge farm, in the Province of Pichincha, Ecuador. For the two primary treatments we used 15 Holstein Friesian cows, fairly adapted to the local conditions, at the age of 60-days after the delivery of the second birth. The control treatment was applied to 14 cows with similar physiological characteristics. The parameters evaluated were: the volume of milk production; the increase in animal weight; and the animal body condition. The data were collected twice a week during the 3 weeks of each feeding experiment....